Dimensi moral dan sosial dalam hikmah pensyariatan ḥadd al-zinā perspektif ali ash-shabuni - Farhan, Ahmad Ali (Maliki Interdisciplinary Journal, 2025)
This article examines the moral and social dimensions embedded in the wisdom behind the legislation of ḥadd al-zinā according to the perspective of Ali ash-Shabuni, a contemporary Qur’anic exegete known for emphasizing public welfare within legalistic interpretations. In modern society, zina is not merely a private moral transgression but a social issue with profound impacts on family integrity, social stability, and lineage preservation. Employing a descriptive-analytical method, this research explores ash-Shabuni’s views as presented in Ṣafwah al-Tafāsīr and Rawā’i‘ al-Bayān to understand how Islamic law aims to safeguard moral order and social harmony through the legal framework of ḥadd al-zinā. The findings indicate that ash-Shabuni interprets the punishment for zina not solely as retribution or deterrence, but as a broader mechanism to preserve human dignity, protect lineage, and strengthen collective morality. This study also highlights the relevance of ash-Shabuni’s socio-ethical hermeneutics in addressing contemporary moral challenges while filling the scholarly gap left by previous studies that predominantly focus on legal-formal aspects without engaging the underlying wisdom of the legislation.